Anti-Inflammatory and Antimicrobial Effects of Herbal Formulation Called Apo-Taat Using Extended-Spectrum ß-Lactamase-Producing Escherichia coli Isolates - Thanakan Kitnithiprapha; Sumalee Panthong; Intouch Sakpakdeejaroen; Sumalee Kondo (The Scientific World Journal)
Pathogens contaminate drinking water in tropical countries causing diarrheal diseases. The conventional treatment for diarrhea is antibiotics. However, overuse and misuse of antibiotics has enabled pathogens to adapt, causing global antibiotic resistance and proliferation of extended-spectrum ß-lactamase-producing Escherichia coli (ESBL-E. coli), which causes diarrhea and high levels of inflammatory cytokines. Apo-taat, consisting of equal proportions of Phyllanthus emblica and Caesalpinia sappan, has been used to treat diarrhea and bloody diarrhea. Its antibacterial activity against E. coli ATCC 25922 has been reported, but its inhibitory effect against ESBL-E. coli has yet to be documented. This study investigated the antibacterial effect of Apo-taat extract against ESBL-E. coli and its anti-inflammatory activity. Antibacterial activity was determined by the microtiter plate–based method. HPLC was used to determine the brazilin and gallic acid contents in Apo-taat extract. Effects of herbal extracts on nitric oxide, IL-6, and TNF-α were investigated in RAW 264.7 cells. Results were that Apo-taat extract showed MIC values against ESBL-E. coli in the range of 0.625 to 2.5 mg/mL. Its 50% inhibitory concentration against nitric oxide and IL-6 production was 83.96 ± 10.60 and 83.06 ± 2.07 μg/mL, respectively, and it had slight inhibition against TNF-α. These findings suggest that Apo-taat may have an antibacterial impact on ESBL-E. coli and anti-inflammatory activity. Furthermore, safety and clinical trials should be conducted in the future.